A solid calcium ion selective electrode and preparation method thereof

By using mesoporous structure and nitrogen-doped carbon-based materials to construct solid calcium ion selective electrodes, the problems of measuring Ca2+ concentration in water quality in the prior art are solved, and the problems of low conductivity of SC materials are achieved Cost, high sensitivity and high selectivity calcium ion detection effect.

CN115389589BActive Publication Date: 2025-02-21GUANGZHOU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211065706.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-02-21
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

The prior art has problems such as time-consuming, expensive instruments and poor conductivity of SC materials when measuring Ca2+ concentration in water quality, and lacks guidelines for improving the interface capacitance of carbon-based SC materials.

Method used

Solid calcium ion-selective electrodes are constructed using carbon-based materials under the synergistic effect of mesoporous structure and nitrogen doping. NMC and PVDF are dispersed in THF solution through preparation method, and then ultrasonic dispersed and applied dropwise onto glass carbon electrodes to form NMC -SC layer and then coated with Ca2+-ISM solution.

Benefits of technology

It has achieved low water layer effect and excellent stability, low cost, high sensitivity and high selectivity, and has great application potential and commercial prospects for calcium ion detection in mineral water and soil leaching fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115389589B_ABST
    Figure CN115389589B_ABST
Patent Text Reader

Abstract

The invention relates to the field of ion analysis sensors and discloses a method for preparing a solid-state calcium ion selective electrode, comprising the following steps: first dispersing silicon dioxide in water by ultrasonic wave, adding 4-aminoantipyrine to the silicon dioxide solution for mixing, adding ferric nitrate, ultrasonic treatment, drying, and heat treatment to obtain substance one; etching the product of substance one in HF solution to remove iron particles and silicon dioxide to form NMC; dispersing NMC and Nafion in ethanol solution, ultrasonic dispersion to obtain solution A, and applying solution A dropwise on a treated glassy carbon electrode, wherein the active material electrode loading is about 1 mg cm ‑2 , drying to obtain a NMC-SC layer; coating the NMC-SC layer with Ca 2+ ‑ISM solution, dried to obtain a solid calcium ion selective electrode; tested Ca in 5 mineral waters and 5 soil leachates 2+ The content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ion analysis sensors, in particular to a solid calcium ion selective electrode and a preparation method thereof. Background Art

[0002] Ca 2+ It is an important ion for the growth and development of organisms and can act as a signal molecule to regulate the absorption of ions by cells and the function of carbohydrate metabolism in organisms. 2+ Real-time, accurate, and persistent monitoring of Ca2+ helps people monitor in real time whether the water quality meets the calcium ion content required by organisms. However, traditional analytical methods (such as spectral analysis) measure Ca2+ off-site. 2+ In the past 20 years, potentiometric sensors based on ion selective membranes (ISMs) have become a popular method for measuring Ca concentration in water due to their simple structure, small size, and light weight. 2+ The main means of ion-to-electrode transition is to use solid contact (SC) materials.

[0003] Currently, a variety of SC materials have been developed, including conductive polymers (CPs), carbon-based materials, metal oxides (MO x ), molecular redox conjugates and precious metals. Among them, CPs have large redox capacitance, but face interference from gas, light or pH. In recent years, the application cost of precious metals is relatively high, and metal oxides (MO x ) are used to replace expensive noble metal materials, but they face the problem of poor electrical conductivity. Carbon-based materials have become the most widely used superconducting materials due to their high electric double layer (EDL) capacitance and hydrophobicity. For example, heteroatom doping and pore engineering are effective methods to improve the EDL capacitance of carbon materials, especially in the field of energy storage. Some typical carbon materials, such as porous carbon, graphene, and carbon nanotubes have been used as SC materials for SC-ISEs (solid contact-ion selective electrodes). However, there is still a lack of a guideline for improving the interfacial capacitance of carbon-based SC materials in the field of SC-ISEs. For this reason, we proposed a solid-state calcium ion selective electrode and its preparation method. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the present invention provides a solid calcium ion selective electrode and a preparation method thereof, which solves the above-mentioned problems.

[0006] (II) Technical solution

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a solid calcium ion selective electrode, comprising a glassy carbon electrode with a diameter of 5 mm, a solution A with a concentration of 10 mg / ml, and Ca 2+ - ISM (Calcium Ion Selective Membrane) solution.

[0008] Solution A included 10 mg NMC (nitrogen-doped mesoporous carbon), 250 μL Nafion, and 750 μL ethanol;

[0009] Ca 2+ -ISM solution includes 3 mL THF (tetrahydrofuran, solvent), 117.72 mg PVC (polyvinyl chloride, solute proportion 32.7 wt%), 235.44 mg NPOE (o-nitrophenyl octyl ether, solute proportion 65.4 wt%), 4.68 mg calcium ion carrier IV (solute proportion 1.3 wt%) and 2.16 mg KTPFB (potassium tetrakis(pentafluorophenyl)borate, solute proportion 0.6 wt%).

[0010] Preferably, the NMC comprises silicon dioxide, water, 4-aminoantipyrine and ferric nitrate.

[0011] A method for preparing a solid calcium ion selective electrode comprises the following steps:

[0012] The first step is to disperse silicon dioxide in water by ultrasonic wave, add 4-aminoantipyrine to the silicon dioxide solution and mix, add ferric nitrate, ultrasonic wave treatment, drying, heat treatment, and obtain substance 1;

[0013] Step 2: Etch the product of substance 1 in HF solution to remove iron particles and silicon dioxide to form NMC;

[0014] Step 3: Disperse NMC and PVDF in THF solution and disperse by ultrasonic to obtain solution A. Apply solution A dropwise on the treated glassy carbon electrode. The active material electrode loading is about 1 mg cm -2 , drying to obtain a NMC-SC layer (nitrogen-doped mesoporous carbon-solid contact layer);

[0015] Step 4: Coating Ca on NMC-SC layer 2+ -ISM solution, dried to obtain a solid calcium ion selective electrode;

[0016] Step 5: Test the Ca content in 5 mineral waters and 5 soil extracts 2+ The content.

[0017] Preferably, the ultrasonic treatment time in the first step is 3 hours and the drying temperature is 85°C;

[0018] The heat treatment condition is 800°C for 3h in an argon atmosphere.

[0019] Preferably, the ultrasonic dispersion in the third step is carried out for 2 hours, and the drying condition is to place the mixture in an oven at 60° C. for half an hour.

[0020] Preferably, the glassy carbon electrode treatment process in the third step is to first polish it on a nylon cloth with 0.3 μm Al2O3 polishing powder, then polish it with 0.05 μm Al2O3 polishing powder after cleaning, and finally wash it with clean water and ethanol.

[0021] Preferably, the drying time in the fourth step is 3 hours.

[0022] (III) Beneficial effects

[0023] Compared with the prior art, the present invention provides a solid calcium ion selective electrode and a preparation method thereof, which has the following features:

[0024] Beneficial effects:

[0025] 1. The solid-state calcium ion selective electrode and its preparation method, the solid-state ion selective electrode based on carbon material with synergistic effect of mesoporous structure and nitrogen doping, has low water layer effect and excellent stability. The above sensor is used to detect calcium ions in mineral water and soil eluent. The sensor has the advantages of low cost, high sensitivity, high selectivity, etc., and has great application potential and commercial prospects.

[0026] 2. This solid-state calcium ion selective electrode and its preparation method are the first to use carbon-based materials under the synergistic effect of mesoporous structure and N doping to construct a solid-state calcium ion selective electrode, and verify the calcium ion concentration in mineral water and soil eluent.

[0027] 3. This solid-state calcium ion selective electrode and its preparation method, due to the influence of mesoporous structure and N doping, NMC has a higher EDL capacitance while maintaining a higher hydrophobicity, no obvious water layer effect is observed and has a higher potential stability, which provides guidance for the development of carbon-based SC-ISEs based on the synergistic effect of mesoporous and nitrogen doping. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of X-ray diffraction of NMC;

[0029] Figure 2 (a) is a schematic diagram of the scanning electron microscope of NMC; (b) is a schematic diagram of the element imaging distribution;

[0030] Figure 3 (a) shows the electrode of NMC-ISEs for Ca 2+(a) is a schematic diagram of the potential response curve; (b) is a schematic diagram of the corresponding potential-calcium ion activity calibration curve;

[0031] Figure 4 (a) shows the NMC-ISEs electrode for the target ion Ca 2+ and (b) schematic diagram of the potential comparison of NMC-ISEs electrodes to interfering ions;

[0032] Figure 5 (a) is a schematic diagram of the water layer test of NMC-ISEs; (b) is a schematic diagram of the long-term potential stability of NMC-ISEs electrodes;

[0033] Figure 6 (a) is NMC at 0.25A g -1 Schematic diagram of charge and discharge test under current density; (b) is a schematic diagram of chronopotentiometry test based on NMC solid-state calcium ion selective electrode;

[0034] Figure 7 (a) is a schematic diagram showing the comparison between the test results of mineral water using a calcium ion sensor constructed based on NMC electrodes and the test results of ion chromatography; (b) is a schematic diagram showing the comparison between the test results of soil eluent using a calcium ion sensor constructed based on NMC electrodes and the test results of ion chromatography. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] See also Figure 1-7 , a method for preparing a solid calcium ion selective electrode, comprising the following steps:

[0037] First, 0.5 g of silica was dispersed in water using ultrasound. Then, 0.5 g of 4-aminoantipyrine was added to the silicon solution and mixed. 0.5 g of ferric nitrate was added as a polymerization inducer, and the mixture was ultrasonically treated for about 3 hours and dried in an oven at 85°C overnight. The powder was heat treated at 800°C in an argon atmosphere for 3 hours. Finally, the product was etched in an HF solution to remove the iron particles and silica to form NMC.

[0038] Scanning electron microscope (SEM) test Figure 2 ), the microstructure of NMC is an irregular thin-sheet structure with porous surface ( Figure 2 a). Elemental imaging analysis shows the presence of C and N elements, which are evenly distributed ( Figure 2 b).

[0039] A glassy carbon electrode (GCE) with a diameter of 5 mm was used as the working electrode, and a platinum wire and a saturated calomel electrode were used as the counter electrode and the reference electrode, respectively. Before use, the glassy carbon electrode was polished on a nylon cloth with 0.3 μm Al2O3 polishing powder, then cleaned and polished with 0.05 μm Al2O3 polishing powder, and finally washed several times with clean water and ethanol.

[0040] All electrochemical tests were performed using a Gamry electrochemical workstation and an EMF6 multi-channel potentiometer.

[0041] Preparation of solid calcium ion selective electrode: First, 10 mg NMC and 250 μL Nafion were dispersed in 750 μL ethanol solution and ultrasonically dispersed for 2 h to a concentration of 10 mg / ml. Finally, 20 μL of the dispersed solution was applied to the treated glassy carbon electrode. The active material electrode loading was about 1 mg cm -2 The electrode was placed in an oven at 60°C and dried for half an hour. The electrode was recorded as NMC-SC layer.

[0042] 3 mL THF, 117.72 mg PVC (32.7 wt%), 235.44 mg NPOE (65.4 wt%), 4.68 mg calcium ion carrier IV (1.3 wt%), 2.16 mg KTPFB (0.6 wt%) were used to prepare Ca 2+ -ISM solution. 50 μL was applied on the NMC-SC layer and dried at room temperature for 3 hours.

[0043] The three-electrode system was used to electrochemically test the charge and discharge performance of NMC electrodes, and the chronopotentiometry test of the calcium ion selective electrode based on NMC was performed. Figure 6 As shown. According to the calculation formula of specific capacitance C s =I×Δt / ΔV, I is the applied current density (0.25A g -1 );Δt is the average time of charge and discharge, ΔV is the potential window, and its specific capacitance is calculated to be 106.6F g -1 When a current of ±1nA was applied to the NMC-based calcium ion selective electrode, the potential drift was only 0.8mV, indicating that it has a strong anti-polarization ability.

[0044] The electrochemical open circuit potential test method was used to test the Ca 2+ The potential response of Figure 3 As shown in the figure, it can be seen that the NMC-ISEs electrode has a high affinity for Ca 2+ The sensitivity is 26.25mV dec -1 , detection limit 10 -5.5M. Meet the testing needs of actual samples.

[0045] Testing the effects of NMC-ISEs on Ca 2+ Selectivity of response. Using the electrochemical open circuit potential test method, the target electrode is tested for interfering ions (Na + ,K + ,NH4 + and Mg 2+ ) and then calculate the respective selectivity coefficients: (Where, E j and E i ,Z j and Z i ,a j and a i Represent the potential, charge number, and ion activity of the interfering ion and target ion respectively; F is the Faraday constant, R is the ideal gas constant, and T is the temperature). The potential of the NMC-ISEs electrode at 0.1M interfering ions and target ions is as follows Figure 4 As shown in a, it can be seen that the potentials of all interfering ions are above the target ion Ca 2+ potential, proving that NMC-ISEs are sensitive to Ca 2+ It has a certain selectivity. The selectivity coefficient for each interfering ion is calculated by the selectivity coefficient formula, as shown in Figure 4 b. + ,K + ,NH4 + and Mg 2+ The selectivity coefficient is calculated to obtain logK ij ≤–3. This is comparable to the selectivity coefficient reported in the literature.

[0046] Figure 5 In the illustration a, the hydrophobicity of the NMC electrode was tested by measuring its contact angle, which was as high as 127.3°, indicating that it has good hydrophobicity. The water layer effect of the electrode and its long-term stability in 0.1M CaCl2 solution were analyzed by electrochemical open circuit potential test. Figure 5 The potential of NMC-ISEs in a was stable in 0.1M MgCl2 and 0.1M CaCl2 after two changes of solution, indicating that it has good capacitance and hydrophobicity, avoiding the water layer effect. Figure 5 b It can be seen that the potential drift of NMC-ISEs over a measurement period of more than 7 days is only 66.95 ± 14.54 μV h -1 , indicating that the electrode potential is stable and can be used for a long time.

[0047] Using NMC as the base of calcium ion selective electrode, the Ca content in 5 mineral waters and 5 soil leachates was tested. 2+Each sample consists of 3 Ca 2+ -SC-ISEs individual test. The test results are compared with the ion chromatography test results. Figure 7 a, 7b. It can be seen that the two measurement results are basically consistent. 2+ The detection accuracy reached more than 85%, proving that the ion selective electrode has good analytical performance.

[0048] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a solid calcium ion selective electrode, characterized in that: The solid calcium ion selective electrode comprises a glassy carbon electrode with a diameter of 5 mm, a solution A with a concentration of 10 mg / ml, and a calcium ion selective membrane Ca 2+ -ISM solution; Solution A included 10 mg nitrogen-doped mesoporous carbon NMC, 250 μL Nafion, and 750 μL ethanol; Ca 2+ -ISM solution includes 3 mL tetrahydrofuran THF, 117.72 mg polyvinyl chloride PVC, 235.44 mg o-nitrophenyl octyl ether NPOE, 4.68 mg calcium ion carrier IV and 2.16 mg potassium tetrakis(pentafluorophenyl)borate KTPFB; The NMC comprises silicon dioxide, water, 4-aminoantipyrine and ferric nitrate; The preparation method comprises the following steps: The first step is to disperse silicon dioxide in water by ultrasonic wave, add 4-aminoantipyrine to the silicon dioxide solution and mix, add ferric nitrate, ultrasonic wave treatment, drying, heat treatment, and obtain substance 1; Step 2: Etch the product of substance 1 in HF solution to remove iron particles and silicon dioxide to form NMC; Step 3: Disperse NMC and Nafion in ethanol solution and disperse by ultrasonic to obtain solution A. Apply solution A dropwise on the treated glassy carbon electrode. The active material electrode loading is 1 mg cm -2 , drying to obtain a nitrogen-doped mesoporous carbon-solid contact layer NMC-SC layer; Step 4: Coating Ca on NMC-SC layer 2+ -ISM solution, and drying to obtain the solid-state calcium ion selective electrode.

2. The method for preparing a solid calcium ion selective electrode according to claim 1, characterized in that: The ultrasonic treatment time in the first step is 3 hours and the drying temperature is 85°C; The heat treatment conditions are 800°C for 3 h in an argon atmosphere.

3. The method for preparing a solid calcium ion selective electrode according to claim 1, characterized in that: The ultrasonic dispersion in the third step is performed for 2 hours, and the drying condition is to place the mixture in an oven at 60° C. for half an hour.

4. The method for preparing a solid calcium ion selective electrode according to claim 1, characterized in that: The glassy carbon electrode treatment process in the third step is to first polish it on a nylon cloth with 0.3 μm Al2O3 polishing powder, then polish it with 0.05 μm Al2O3 polishing powder after cleaning, and finally wash it with clean water and ethanol.

5. The method for preparing a solid calcium ion selective electrode according to claim 1, characterized in that: The drying time in the fourth step is 3 hours.

Citation Information

Patent Citations

  • Metal-free nitrogen-doped functionalized mesoporous carbon catalyst and preparation method and applications thereof

    CN103566961A

  • Potential type microelectrode sensor with universality as well as preparation and application of potential type microelectrode sensor

    CN112213368A